2014
DOI: 10.1177/1535370214561588
|View full text |Cite
|
Sign up to set email alerts
|

Role of WW domain proteins WWOX in development, prognosis, and treatment response of glioma

Abstract: Glioblastoma multiforme (GBM) is the most aggressive and malignant brain tumor. Delicate microenvironment and lineage heterogeneity of GBM cells including infiltration, hypoxia, angiogenesis, and stemness make them highly resistant to current conventional therapies, with an average life expectancy for GBM patients of less than 15 months. Poor response to cytotoxic agents of GBM cells remains the major challenge of GBM treatment. Resistance of GBM to clinical treatment is a result of genomic alternation and der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 124 publications
0
6
0
Order By: Relevance
“…We have also observed a tendency of WWOX gene mRNA to decrease between grade 1 and 2, FIGO stage 1 and 2, and thus it is correlated with deeper myometrial invasion (22). Much data from previous studies demonstrate WWOX protein participation and regulation of various processes involved in tumor development and progression (23)(24)(25)(26)(27). One of these processes is epithelial-mesenchymal transition (EMT), Yan and Sun indicated that the WWOX gene may reverse the EMT in ovarian cancer stem cells by regulating the expression of two EMT factors, Elf5 and Snail (28).…”
Section: Introductionmentioning
confidence: 61%
“…We have also observed a tendency of WWOX gene mRNA to decrease between grade 1 and 2, FIGO stage 1 and 2, and thus it is correlated with deeper myometrial invasion (22). Much data from previous studies demonstrate WWOX protein participation and regulation of various processes involved in tumor development and progression (23)(24)(25)(26)(27). One of these processes is epithelial-mesenchymal transition (EMT), Yan and Sun indicated that the WWOX gene may reverse the EMT in ovarian cancer stem cells by regulating the expression of two EMT factors, Elf5 and Snail (28).…”
Section: Introductionmentioning
confidence: 61%
“…The task of determining the nature of WWOX in GBM is still considered to be at the initial stage [ 57 ], but the influence of this gene on the malignant phenotype of GBM has already been reported [ 33 ]. Because most of the available in vitro research does not consider multiple cellular models of GBM or a wide range of investigated biological assays, the present study aimed to determine the main processes by which WWOX exhibits anticancer properties in GBM, while taking into account the phenotypic heterogeneity between cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…One of the genes affecting both cytoskeleton and GBM is WW domain-containing oxidoreductase (WWOX), a haploinsufficient tumor suppressor described in many cancers, including GBM, for which it impairs malignant phenotype [17]. In the brain tissue, WWOX can be summarized as a global modulator of transcription and an important regulator of differentiation and maintenance [18]; this is complemented with the prognostic relevance of WWOX [19]. It is also an important modulator of metabolic pathways, regulating the synthesis of amino acids and lipids but also glycolysis or Krebs cycle.…”
Section: Introductionmentioning
confidence: 99%
“…For GBM, it has been found that WWOX downregulation may be a result of promoter hypermethylation or loss of heterozygosity (LOH); the latter is related to tumor progression and contributes to 20% of gliomas [22]. Determining the role of WWOX in GBM is thought to be in the initial state [19]; hence, profound research is needed, especially in the cytoskeleton-related context, which remains enigmatic. Available data indicate that WW domain of WWOX collaborates, e.g., with dystroglycan, a transmembrane protein that interacts with utrophin and dystrophin, which also communicate with actin [23].…”
Section: Introductionmentioning
confidence: 99%